Analysis of Deciduous and Permanent Teeth of Children from Brno of 1-15 years of Age with the Focus on Frequency of Dental Caries and Teeth Eruption - J. Huták (Czech Dental Chamber, 2012)
Introduction: Dental caries experience is a very common disease, which needs to be prevented even at children's age. Aim: The aim of the retrospective, epidemiological, sectional study is to conduct a survey on teeth eruption and dental caries experience in Brno children and to compare the dental caries experience results with the results of countrywide surveys that were carried out in 2003 and 2006 in the CR (VÚS - Institute of Dental Research and ÚZIS - Institute of Health Information and Statistics of the CR), as well as with the results from chosen countries from the WHO database. Methods: The sample of the study is represented by 860 Brno children - 424 boys and 436 girls aged 1-15 years. To compare the dental caries experience in Brno children with this feature in children from the VÚS and ÚZIS in 2003 and 2006 and the international comparation, the DMF index per person was used. Results:* Dental eruption in Brno boys/girls - there was no difference in deciduous teeth eruption, at the age of 10.00-10.99 there is a higher number of erupted teeth in boys and at the age of 11.00 to 11.99 in favour of higher number of erupted teeth in girls.* Dental caries experience in Brno boys/girls - there was a lower caries experience in temporary dentition on the median basis at the age of 7.00-7.99 in boys. In the permanent dentition on the median basis there was a lower caries experience in girls at the age of 7,00-7,99.* Teeth eruption and caries experience among boys and girls (VÚS and ÚZIS) from 2003 and Brno boys and girls - there was no difference in permanent dentition eruption, but there was a difference in lower caries experience in deciduous teeth in boys aged 5.00-5.99 than in girls. At the age of 12.00-12.99 there was a difference in a higher number of erupted permanent teeth in Brno boys, but there was no difference in dental caries experience in permanent teeth. At the age of 15.00-15.99 there was neither a difference in eruption nor in caries experience in permanent teeth.* Permament dentition caries experience in children (VÚS and ÚZIS) from 2003 / Brno children - there was no difference at the age of 12.00-12.99 and 15.00-15.99.* Permanent dentition caries experience in children (VÚS and ÚZIS) - JMK (South Moravian Region) from 2006 / Brno children - there was no difference at the age of 12.00-12.99 and 15.00-15.99.* Dental caries experience DMFT (in the CR used as KPE per person) in chosen European countries, where at the age of 12 the Brno children from 2010 (KPE 2.09) have a lower permament dentition caries experience than the average caries experience in the CR in 2002 (KPE 2.5), from 2003 (KPE 2.96) and from 2006 (KPE 2.56). Conclusions: Brno children aged 1.00-15.99 achieved similar teeth eruption caries experience results as the results of the survey carried out by VÚS and ÚZIS, with the exception of the differences at the age of 7, 10 and 11 years.